The importance in DNA barcoding of the regions which is covering rRNA genes and its sequences in the genus Quercus L. - Aykut, Yilmaz (Bangladesh Journal of Plant Taxonomy, 2020)
Turkey with 18 oak (Quercus) species is one of the richest country according to species number and diversity. The most important reason of the species diversity in Turkey is its location and geomorphological structure which increase climatic effects and seperate Turkey into different phytogeographic regions. Furthermore, hybridization behaviours which frequently observed between oak species, genetic drift, gene flow and ecological factors cause morphological variations in the plants species. All of these factors make it difficult to define the species concept for plant groups like oaks. Therefore, the region covering 18S rRNA gene/ ITS1/ 5.8S rRNA gene/ ITS2/ 25S rRNA gene and secondly intergenic spacer (IGS)/ 5S rRNA gene for barcoding were obtained from genbank and used as a useful tool for the determination and solution of the phylogenetic relations of taxonomically problematic species, also these barcoding regions were compared with each other according to species recognition ability for oak species. As a result, it can be stated that both barcoding regions have high variable sites based on sequence information to identify the species and evaluate relationships of species studied. Bangladesh J. Plant Taxon. 27(2): 261-271, 2020 (December)